2013
DOI: 10.1111/bjh.12347
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy of sustained eculizumab treatment in patients with paroxysmal nocturnal haemoglobinuria

Abstract: Paroxysmal nocturnal haemoglobinuria (PNH) is characterized by chronic, uncontrolled complement activation resulting in elevated intravascular haemolysis and morbidities, including fatigue, dyspnoea, abdominal pain, pulmonary hypertension, thrombotic events (TEs) and chronic kidney disease (CKD). The long-term safety and efficacy of eculizumab, a humanized monoclonal antibody that inhibits terminal complement activation, was investigated in 195 patients over 66 months. Four patient deaths were reported, all un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
357
1
21

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 329 publications
(407 citation statements)
references
References 31 publications
22
357
1
21
Order By: Relevance
“…Our study was not designed to assess non-study procedure-related AEs. However, investigators related three mild AEs (fatigue, arthralgia, and headache) in one patient as probably related to eculizumab; these AEs were not unexpected since they have been reported in previous clinical studies [4][5][6][7]. In summary, this analysis demonstrates that long-term treatment with commercial eculizumab in patients with PNH is associated with minimal risk for the development of HAHAs.…”
Section: Assessment Of Human Antihuman Antibodies To Eculizumab Aftersupporting
confidence: 66%
See 3 more Smart Citations
“…Our study was not designed to assess non-study procedure-related AEs. However, investigators related three mild AEs (fatigue, arthralgia, and headache) in one patient as probably related to eculizumab; these AEs were not unexpected since they have been reported in previous clinical studies [4][5][6][7]. In summary, this analysis demonstrates that long-term treatment with commercial eculizumab in patients with PNH is associated with minimal risk for the development of HAHAs.…”
Section: Assessment Of Human Antihuman Antibodies To Eculizumab Aftersupporting
confidence: 66%
“…This current laboratory study, M07-003 (registered at http://www.clinical trials.-gov as NCT01412047), addresses a postapproval commitment to the FDA and the European Medicines Agency (EMA) to examine immunogenicity of eculizumab after longterm treatment. The development of neutralizing and non-neutralizing HAHAs associated with eculizumab use was assessed in patients with PNH who participated in the open-label, long-term study E05-001 [7]. Briefly, the study included 195 patients with PNH who participated in three prospective trials: a phase two pilot study [5]; and two phase three studies [4,6].…”
Section: Assessment Of Human Antihuman Antibodies To Eculizumab Aftermentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers concluded that long-term treatment with eculizumab resulted in sustained improvement in patient's outcome by rapidly reducing hemolysis and significantly reducing the frequency of severe and life-threatening morbidities, improving patient's survival [25], which is corresponding to the study done by Kelly et al [19].…”
Section: The Efficacy Of Eculizumabmentioning
confidence: 85%